Phase Behaviour and Physical Properties of Sulphonated Methyl Ester and Fatty Alcohol Ether Sulphate Mixtures. - Husin, Mohd Zaihanif (2007)
Sulphonated Methyl Ester (SME) and Fatty Alcohol Ether Sulphated (FAES) are anionic surfactants produced from palm oil. SME and FAES are widely used in detergent but their phase behaviour in ternary phase system is little known. The phase behaviour in ternary system has been studied at 70°C under visual observation by polarizing light and they were confirmed by polarization microscope. The microspical study of the composition through polarized light enables identification of the mesomorphic structures present in the system. The study of ternary phase system in combination of SME/ FAES/ Water, SME/ FAES/ 2% NaCl Solution, SME / FAES (60/40)/ Propylene Glycol/ 2% NaCl Solution and SME / FAES (60/40)/ Soap/ 2% NaCl Solution at 70°C. The optical pattern of lamellar liquid crystals has shown a maltese crosses, oily streak and striated textures when observed under a polarizing microscope The study of ternary system leads to the understanding of physico-chemical aspects and allows the contribution of the different components to a detergent formulation to be developed. This formulation was formulated at the liquid crystalline region which was confirmed via polarizing microscope. Liquid crystal is usually highly stable against phase separation and effective in the removal of oily and greasy soil. The formulated liquid detergents, i.e. liquid dish washing, gel dish washing, hand liquid soap, floor cleaner and liquid laundry detergent were found to have comparable or slightly better properties compared to commercials samples in terms of detergency, wetting power, foaming power and stability. The pH and viscosity are comparable with the commercial product.